Plan de negocios para la creación de una empresa que oferte servicios de monitoreo de incidentes informáticos llamado SOC (security operation center) para instituciones financieras en la ciudad de Quito - Pulgar Montero, Renato Sebastián (2016)
This business plan intented to solve and minimize operational risk of computer security systems on financial institutions, which are prone to attacks by hackers or organized groups that are looking forward economic benefits and recognition for their criminal acts. Moreover, this paper aims to identify opportunities and threats to compete in a growing industry, against to companies with foreign capital and years of experience in the market. Technological changes and globalization make developing countries, as Ecuador, have not faced significant cyber-attacks in public or private industries becoming vulnerable to new criminal technological forms from people and countries with an infrastructure, knowledge and technology capable of corrode informatics systems of states, which are not prepared. This business plan propose the creation of an enterprise called Owl SOC, which want to introduce a focused service on providing security to financial institutions of all kinds in the city of Quito 24 hours a day, 7 days a week, and 365 days a year.